Aisyiyah Gebang Role in Overcoming the Problems of Women and Children - Putri Permata Sari; Efrillita Sampurno; Afrelya Rindi; Rika Ayu S.; Izzatur R. (Proceedings of The ICECRS, 2020)
Aisyiyah, a Muhammadiyah women's movement that has been recognized and felt its role in society. Aisyiyah as one of the first autonomous organizations born from Muhammadiyah that has the same goals as Muhammadiyah. Aisyiyah has a special strategy program that has a future outlook on women and children. The role and function of Aisyiyah from time to time continues to grow and provide benefits for the improvement of the dignity of Indonesian women and children. The very real result is that in Gebang village, there is now a form of business charity consisting of a-qur'an Al-furqon educational park, then there is also the Islamic center Al-falah gebang youth movement. In addition to the many results of the form of business charity, but there are also problems of women and children, such as women whose husbands have died and children who are willing to work out of school to help their mothers who are no longer able to work.